Next Generation Sequencing in Cancer Research Volume 1: Decoding the Cancer Genome - Wu, Wei; Choudhry, Hani (Springer New York : Imprint: Springer, 2013)
Next Generation Sequencing (NGS) technology has placed important milestones in the life science and changed the direction in biomedical science inclucing cancer. Scientists around the world are attempting to find the root cause of cancer and they are looking for more direct and effective means to cure cancer. This journey to conquer cancer is more optimistic now with the unfolding of the cancer genome. This book focuses on the application of various NGS in the frontier cancer genome research. The 18 chapters in this volume have been written by scientists with many outstanding contributions in their area and the join effort has created comprehensive insightful view on (1) Overview of next generation sequencing technology in cancer genome research (2) Genome regulation and targeted sequencing in cancer (3) RNA transcriptome (coding and non-coding) in cancer genome (4)The challenges of computational biology for cancer genome study. This book is a state-of-the-art reference to all scientific researchers and onologists who are interested in the understanding of the cancer initiatome at whole genome scale and to those are keen to translate the 'base pairs to bedside' for better management of cancer patients in the era of personalized medicine.